Health-related quality of life among patients undergoing chronic disease management: A cross-sectional study - Nia Kurnia Sholihat, Vitis Vini Fera Ratna Utami (Journal of Applied Pharmaceutical Science, 2020)
The aim of this study is to evaluate the health-related quality of life (HRQOL) of patients with diabetes and hypertension, participating in the Chronic Disease Management Program (Prolanis) in Purwokerto Regency, Indonesia, using the five-level version of the EuroQol five-dimension instrument (EQ-5D-5L). A cross-sectional study was conducted on 267 diabetic and 349 hypertensive patients in six community health centers, using the Indonesian version of the EQ-5D-5L. The EQ-5D-5L utility index was calculated using the Indonesian value set as well as the percentages of the problem in each dimension. The statistical analyses were performed to identify the differences in the EQ-5D utility index between diabetes and hypertension and in the study characteristics. The mean EQ-5D-5L score among diabetic patients was 0.879 ± 0.115, whereas for hypertensive patients, it was 0.879 ± 0.116. Separately, the EQ visual analog scale (EQ-VAS) for diabetes and hypertension was 80.030 ± 12.893 and 79.180 ± 14.223, respectively. The most frequently reported problems were pain/discomfort (67.42% in diabetes and 62.75% in hypertension) followed by anxiety/depression (36.33% in diabetes and 41.11% in hypertension). There was no significant difference between the utility index values (p = 0.056) nor EQ-VAS scores (p = 0.573) of diabetic and hypertensive patients. The work status had a significant effect on the HRQOL of diabetic patients (p = 0.016). This study suggests that healthcare professionals should pay more attention to pain and depression management to improve the lives of patients with chronic disease.
Keywords: EQ-5D-5L, health-related quality of life, diabetes, hypertension, Indonesia, chronic disease management.